2022
DOI: 10.1186/s13765-022-00722-w
|View full text |Cite
|
Sign up to set email alerts
|

CircTRRAP (hsa_circ_0081234) participates in prostate cancer progression and glycolysis by HOXA1 via functioning as a miR-515-5p sponge

Abstract: Dysregulated circular RNAs (circRNAs) are implicated in prostate cancer (PCa) progression. Hsa_circ_0081234 (circTRRAP) has been revealed as a facilitator in PCa, but the mechanisms associated with circTRRAP in PCa progression are largely unclear. The present study was to explore the regulatory mechanism of circTRRAP-mediated PCa progression. A total of 50 PCa tissues and normal tissues were collected. RNA levels of circTRRAP, microRNA (miR)-515-5p and homeobox A1 (HOXA1) were detected by quantitative real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Guan et al [ 301 ] studied the pathophysiological processes underlying CircTRRAP in PCa development. A recent study found that circTRRAP was increased in PCa specimens with spinal metastasis.…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%
See 4 more Smart Citations
“…Guan et al [ 301 ] studied the pathophysiological processes underlying CircTRRAP in PCa development. A recent study found that circTRRAP was increased in PCa specimens with spinal metastasis.…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%
“…CircTRRAP enhances PCa progression and plays a role in glycolysis in PCa cells. It enhances the ability of PCa cells to invade and glycolysis via the miR-515-5p/HOXA1 pathway [ 301 ]. Silencing circTRRAP reduced glucose and lactate production uptake in PCa cells, suggesting circTRRAP's involvement in glycolysis in PCa [ 301 ].…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%
See 3 more Smart Citations